SINKRONISASI NORMA HUKUM PELAKSANAAN PROGRAM NASIONAL AGRARIA (PRONA) DENGAN POLA PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) - Ismail Ismail (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2019)
The research is motivated by the existence of conflicting norms between Ministerial Regulation ATR / BPN Number 6 of 2018 concerning PTSL with PP Number 24 of 1997 concerning Land Registration in achieving all land certificates in 2025. Therefore the President issued a nawacita that is through the National Agrarian Program or (PRONA) with the PTSL pattern. This research uses Normative Juridical Research Type. Furthermore, the results of the research show that Synchronization between Ministerial Regulation ATR / BPN Number 6 of 2018 concerning PTSL compared with PP Number 24 of 1997 concerning Land Registration based on Article 8 Paragraph (1) and (2) of Law Number 12 of 2011 concerning Formation of Regulations This unconstitutional legislation is because the contents do not violate or are not in conflict with Government Regulation Number 24 of 1997 concerning Land Registration only to achieve the goal of land certification in Indonesia in 2025 which has reached 100% then the existence of Ministerial Regulation ATR / BPN Number 6 2018 concerning PTSL only shortens the requirements contained in PP No. 24 of 1997 concerning Land Registration not to eliminate or even eliminate.Keywords: Synchronization, National Agrarian Program, Land Registration, Implementation